Literature Review of the Implementation of Digital Marketing Strategies for MSME Actors in Indonesia - MA Mursidi; Dziky Ridhwanullah (Nur Science Institute, 2023)
Progress digital technology has big impact For various sectors of life. With utilise matter these MSME actors in Indonesia can have opportunity more big. For example in promote goods or services. How is the digital marketing strategy implemented by MSME actors in Indonesia. The literature review method was applied to the research this. Based on results study influential digital marketing significant to MSME actors in Indonesia if using digital marketing with know the strategies and methods management For jack the sales. Temporary No influential for MSME actors who use digital marketing however tend passive as well as No know method use and only just follow the trend.